Incremental cost of nosocomial bacteremia according to the focus of infection and antibiotic sensitivity of the causative microorganism in a university hospital. Issue 17 (April 2017) - Riu, Marta; Chiarello, Pietro; Terradas, Roser; Sala, Maria; Garcia-Alzorriz, Enric; Castells, Xavier; Grau, Santiago; Cots, Francesc
Abstract : Abstract: To estimate the incremental cost of nosocomial bacteremia according to the causative focus and classified by the antibiotic sensitivity of the microorganism. Patients admitted to Hospital del Mar in Barcelona from 2005 to 2012 were included. We analyzed the total hospital costs of patients with nosocomial bacteremia caused by microorganisms with a high prevalence and, often, with multidrug-resistance. A control group was defined by selecting patients without bacteremia in the same diagnosis-related group. Our hospital has a cost accounting system (full-costing) that uses activity-based criteria to estimate per-patient costs. A logistic regression was fitted to estimate the probability of developing bacteremia (propensity score) and was used for propensity-score matching adjustment. This propensity score was included in an econometric model to adjust the incremental cost of patients with bacteremia with differentiation of the causative focus and antibiotic sensitivity. The mean incremental cost was estimated at [Euro sign]15, 526. The lowest incremental cost corresponded to bacteremia caused by multidrug-sensitive urinary infection ([Euro sign]6786) and the highest to primary or unknown sources of bacteremia caused by multidrug-resistant microorganisms ([Euro sign]29, 186). This is one of the first analyses to include all episodes of bacteremia produced during hospital stays in a single study. The study included accurate information about the focus and antibiotic sensitivity of the causative organism and actual hospital costs. It provides information that could be useful to improve, establish, and prioritize prevention strategies for nosocomial infections. Abstract : Supplemental Digital Content is available in the text